Czech Consumers in the Plant-Based Market : Motivations and Barriers - Limarenko, Iryna; Lhotáková, Markéta, 1971-; Halík, Jaroslav, 1961-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores the topic of plant-based products and Czech consumers’ preferences. The main aim of the thesis is to characterize the behavior of Czech consumers on the plant-based products market on the basis of a quantitative study. The theoretical part provides a detailed overview of the characteristics of plant-based products, their historical development and relevance within the context of sustainability. It also outlines main aspects of consumer behavior and specifics of Czech consumers. The Czech market is analyzed in terms of its current state, consumer segmentation and major market players. The practical part is based on quantitative research carried out through an online questionnaire, which collected responses from 467 individuals. The findings reveal that awareness of plant-based products is relatively high among younger and educated consumers. However, these products are not yet part of a regular diet for most people. The main factors influencing Czech consumers’ purchasing decisions are health benefits, price and taste. So, the biggest barriers in buying plant-based products remain high prices, limited product variety and concerns about flavor and quality. The thesis concludes with a set of recommendations for industry stakeholders. It was proposed to improve affordability of plant-based products, expand product offerings, enhance taste and sensory quality, and build trust in eco-labels and sustainability.
Vedoucí práce: Markéta Lhotáková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses